Feyerabend on Pluralism, Contingency, and Humility - Kidd, Ian James (Filozoficzne Aspekty Genezy, 2023)
Throughout the writings of Paul Feyerabend, there are constant references to the historical contingency of the scientific enterprise, often accompanied by philosophical claims about the significance of that contingency. This paper presents those contingentist claims, situates them in the context of more recent work on the contingency of science, and offers an interpretation of their significance. I suggest that Feyerabend’s sense of contingency was connected to his defences of pluralism, and also to the “conquest of abundance” narrative developed in the very late writings.